Hardware Removal in Maxillofacial Trauma: A Retrospective Study. (23rd June 2021) - Aramanadka, Chithra; Kamath, Abhay T.; Srikanth, G.; Pai, Deepika; Singla, Nishu; Daundiyal, Shriya; Desai, Avani
Abstract : Background . Miniplates are commonly used for the fixation of maxillofacial fracture segments. Removal of the hardware is controversial. A retrospective study of medical records was performed to observe the reasons for plate removal. Materials and Methods . A 10-year retrospective study of medical records was performed. Demographics, type of fracture, location, type of miniplate used, the time gap between the insertion and removal, and causes of hardware removal were assessed. Results . About 1472 patients had undergone internal fixation for the facial fractures. Stainless steel miniplate was used in 489 patients, and titanium was used in 983 patients. Out of the 42 cases, 22 cases involved the removal of titanium hardware and 20 patients involved the removal of stainless steel hardware. Infection/osteomyelitis was the main cause of hardware removal. The maximum amount of hardware failure was in the mandible. 78.6% of hardware removal was performed in males. Conclusion . Based on our study, routine removal of titanium miniplates can be performed in children to avoid growth disturbances, not indicated in adult patients unless symptomatic.